Game of clones: Diverse implications for clonal hematopoiesis in lymphoma and multiple myeloma. (November 2022) - Meier, Jeremy; Jensen, Jeffrey L.; Dittus, Christopher; Coombs, Catherine C.; Rubinstein, Samuel
Abstract: Clonal hematopoiesis (CH) refers to the disproportionate expansion of hematopoietic stem cell clones and their corresponding progeny following the acquisition of somatic mutations. CH is common at the time of diagnosis in patients with blood cancers, including multiple myeloma (MM) and lymphoma. The presence of CH mutations correlates with IL-6 mediated inflammation and may result in lymphoma or MM modulation through microenvironment effects or by manifestations of the mutations themselves within the founding tumor clone. As might be expected with a variety of mutations and multiple potential mechanisms, CH exerts context-dependent effects, being protective in some settings and harmful in others. Though CH is very common in patients with hematologic malignancies, how it intersects with therapy and the natural disease course of these cancers are active areas of investigation. In lymphomas and MM specifically, patients have high rates of CH at diagnosis and are subsequently exposed to therapies, such as cytotoxic chemotherapy, that can cause CH progression to overt hematologic malignancy. The expanding diversity of treatment modalities for these cancers also increases the opportunities for CH to impact clinical outcome and modulate clinical responses. Here we review the basic biology and known health effects of CH, and we focus on the clinical relevance of CH in lymphoma and MM.